2019
DOI: 10.1556/0406.20.2019.004
|View full text |Cite
|
Sign up to set email alerts
|

Review of attachment interventions in eating disorders: Implications for psychotherapy

Abstract: Background: Attachment theory has been used in personalized treatments since decades. It is a major framework for understanding images of the self, affect regulation, reflective functions and interpersonal relationships. The improvement of attachment functioning is associated with positive treatment outcomes in eating disorders. However, attachment interventions have not been summarized in their psychotherapy. Aims: The aim was to review the relevance of attachment features in the psychotherapy of eating disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 94 publications
0
4
0
Order By: Relevance
“…Szalai [31] conducted the review using the terms "eating disorder" and "attachment" from 1987 until 2017. From the 320 matches, he used 50 relevant studies which he integrated into his article.…”
Section: Relationship Questionnaire (Rq)mentioning
confidence: 99%
“…Szalai [31] conducted the review using the terms "eating disorder" and "attachment" from 1987 until 2017. From the 320 matches, he used 50 relevant studies which he integrated into his article.…”
Section: Relationship Questionnaire (Rq)mentioning
confidence: 99%
“…Illing et al (2010) found that higher attachment anxiety was significantly correlated with greater severity of ED symptoms and worse treatment outcomes in a clinical sample. Different studies proved that attachment anxiety and avoidance were associated with higher levels of ED symptoms (Szalai, 2019), whereas the decrease of attachment anxiety was associated with lower symptom severity and better treatment outcomes (Tasca, 2019). A recent pilot study (Zeeck et al, 2021) on mentalization-based treatment has shown that only 5.3% of the sample ( n = 38) with ED showed secure attachment, whereas most of the sample (composed of young women) had an avoidant-withdrawn attachment style (47.4%).…”
Section: Attachment and Eating Disordersmentioning
confidence: 99%
“…Additionally, no significant difference was observed between those with abnormal nutritional status and those with normal nutritional status in terms of experiencing eating disorders. 10 Adolescents with a higher BMI tend to feel uncomfortable or ashamed of their body shape. The notion of a slim and slender physique being deemed the ideal body shape can lead adolescents to control or reduce their food intake based on their own thoughts, often resulting in disordered eating behaviors.…”
Section: Original Articlementioning
confidence: 99%
“…8 The interconnection between body perception, eating disorders, and nutritional status needs to be understood to identify the complex issues that impact the psychological development of adolescents. 7,9,10 The Austria Academy for Eating Disorders (2006) states that various forms of eating disorders are reported to occur in 4.0% of adolescents and young adults. Approximately 95% of patients are females, and these disorders typically develop during adolescence and sometimes in adulthood.…”
Section: Introductionmentioning
confidence: 99%